Treatment of class II malocclusion and unerupted upper canines with self-ligating appliance - Rita Catia Brás Bariani; Carlos Henrique Guimarães; Wilana Silva Moura; Cristina Lucia Feijó Ortolani; Josß Fernando Castanha Henriques; Silvio Augusto Pereira-Bellini (Wolters Kluwer Medknow Publications, 2018)
Treatments without tooth extractions have become more popular over the last two decades. In this context, expansion of the maxillary arch is an interesting treatment option for cases in which space is required and other factors not favoring extractions (such as the facial profile) are present. According to several authors, this posterior expansion can be obtained using a system comprising self-ligating brackets and superelastic nickel-titanium arches. The present article aims to report a case of a young patient with Class II, Division 2 malocclusion, with impacted upper canines and significant arch length-tooth discrepancy. Methods: The case was treated by means of a passive self-ligating appliance in association with Class II elastics and coil spring for distalizing the molars. This treatment alternative was effective for correcting Class II and obtaining space to correct tooth positioning.